Open Neuroscience:Challenging Scientific Barriers With Open Source & Open Science tools - Maia Chagas, Andre (My University, 2020)
Presentation given at the SONA/Trend in Africa webinar series. It discusses how researchers should be embracing open source and open science tools to tackle scientific barriers.
Keywords: MEDICINE::Morphology, cell biology, pathology::Cell biology::Neuroscience; open source hardware; open science